If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+19-4=5(5x+4)
We move all terms to the left:
6+19-4-(5(5x+4))=0
We add all the numbers together, and all the variables
-(5(5x+4))+21=0
We calculate terms in parentheses: -(5(5x+4)), so:We get rid of parentheses
5(5x+4)
We multiply parentheses
25x+20
Back to the equation:
-(25x+20)
-25x-20+21=0
We add all the numbers together, and all the variables
-25x+1=0
We move all terms containing x to the left, all other terms to the right
-25x=-1
x=-1/-25
x=1/25
| X+30+x+30-5=x | | 10(x+1)=7(x/4) | | 4.3x+(66.3/59.659)=33.07 | | (3)/(x)=(9)/(4x)+3 | | 3x-4x=43 | | 2x+5(5x-7)=47 | | 13+2(x-6)=19-3(x+1) | | 2.1(z+1)-3.6=6.27 | | 2x+9=(2x+9)(2x+9) | | x(3x-9)=(3x+6)(x-7) | | u+3.2=6.3 | | -(3x+2)+5=-2+1+9x | | 1.56(c+5)+9.97=5.29 | | –6+3m=4m | | r-4.7=3.1 | | 3x-15=8x+25 | | k^2-k+48=0 | | 20-x2=16 | | 3(2x-5)=4x-9 | | 6=-w|8 | | 08r=64 | | 4x-2(4x+30)=16x | | 9(3c-1)+4=49 | | 2y+9.9=1.1 | | X-21x=24 | | x+(x+10)+(3x)=180 | | -4(2x-8)=-8x-32 | | 4x+6=-8x+8 | | 13+2(x-6)=19-3(x+10 | | 8=-8(y+1) | | X-21x=23.7 | | 2-6x=2(x+1) |